Urinary tract stone disease - Nagaraja Rao, P. 1910-.; Preminger, Glenn M.; Kavanagh, John P.; SpringerLink (Online service). (London New York Springer, 2011)
Urinary Tract Stone Disease covers the entire subject of urinary stone disease from basic sciences to medical and surgical treatment of stones. The surgical management of urinary stone disease has advanced significantly since the introduction of shock wave lithotripsy (SWL), percutaneous nephrolithotomy (PCNL), ureteroscopy (URS), and more recently retrograde intra-renal surgery (RIRS) with small, flexible fibre-optic ureteroscopes. As a result, cutting for stones has become a rare procedure. These minimally invasive techniques are now also used in the paediatric population with great safety and success. This book consists of 60 chapters divided into 9 sections. The first 3 sections are devoted to basic sciences on subjects ranging from epidemiology of urinary calculi, to shock wave physics. The fourth section deals with diagnostic, laboratory, and research methods in the diagnosis and investigation of stones. Stone disease in children is dealt with in chapter 5, followed by 3 sections on surgical management of stones. Finally, there is an entire section on medical management of stones. With highly illustrated diagrams, photographs, and X-ray images throughout, this book is an excellent reference for urologists, nephrologists and non-medical scientists.
Basic sciences I: -- Epidemiology -- Genetics and Molecular Biology of Renal Stones -- Physico-Chemical Aspects of Uro-Crystallization and Stone Formation -- The Possible Roles of Inhibitors, Promoters and Macromolecules in the Formation of Calcium Kidney Stones -- Renal Cellular Dysfunction/Damage and the Formation of Kidney Stones -- Interaction of Stone Components with Cells and Tissues -- Randall?s Plaques -- Dietary Factors -- Obesity, Metabolic Syndrome, and Stones -- Stone Diseases in Animals -- Pathogenesis of Stones: Summary of Current Concepts -- Basic sciences II: -- Calcium Metabolism and Hypercalciuria -- Vitamin D Metabolism and Stones -- Urinary Citrate and Citrate Metabolism -- Uric Acid Metabolism and Uric Acid Stones -- Oxalate Metabolism and the Primary Hyperoxalurias -- Cystinuria and Cystine Stones -- Urinary Infection and Struvite Stones -- Drug-Induced Renal Stones -- Endemic Bladder Stones -- Economic Implications of Medical and Surgical Management -- Basic sciences III: -- What Are Shock Waves? -- Extracorporeal Shock Wave Lithotriptors -- Biological Effects Produced by High-Energy Shock Waves -- Intracoporeal Non-Laser Lithotripsy -- Laser Lithotripsy Physics -- Alternative Laser Energy Sources Clinical Implications -- Diagnostic and labarotory methods: -- Imaging for Stones -- Urinary Stone Analysis -- Risk Indices -- Blood and Urinary Tests in Stone-Formers -- Crystallization and Other Studies -- Experimental Models for Investigation of Stone Disease -- Clinical Trials in Stone Disease -- Paediatric stone disease: -- Epidemiology of Pediatric Urolithiasis -- Metabolic Stone Disease in Children -- The Role of Minimally Invasive Techniques -- Surgical management I: -- Indications for Surgical Removal, Including Asymptomatic Stones -- Extracorporeal shock wave lithotripsy: -- Extracarporal Shock Wave Lithotripsy for Renal Stones -- Extracorporeal Shock Wave Lithotripsy for Ureteral Stones -- Surgical management II: -- Endoscopy: -- Percutaneous Nephrolithotomy -- Ureteroscopy for Ureteric Stones -- Indications for and Technique of Retrograde Intrarenal Surgery for Renal Stones -- Urolithiasis in Pregnancy -- Surgical Management of Urolithiasis in Transplanted Kidneys -- Stents and Stenting -- Flexible Ureterorenoscopy: Tips and Tricks -- Training Implications for Stone Management -- Surgical management III: Open surgery: -- Open Surgery to Remove Stones When And How -- Autotransplantation and Ureteric Replacement - In Whom and How? -- Liver and Renal Transplantation in Primary Hyperoxaluria -- Chemolytic Treatment of Patients with Urinary Tract Stones -- Medical management -- Establishment and Management of a Stone Clinic -- Medical Expulsive Therapy -- Metabolic Investigations: When and In Whom -- Medical Management of Idiopathic Calcium Stone Disease -- Medical Management: Uric Acid and Cystine Stones -- Medical Management of Struvite Stones -- Dietary Assessment and Advice -- Stone Management in the Presence of Morbid Obesity.
Electronic reproduction.
Keywords: Urinary organs -- Calculi; Urinary organs -- Calculi -- Treatment; Electronic books